Interior design on edge history, theory, praxis - Morawski, Erica (Abingdon, Oxon : Routledge, 2024)
Interior Design on Edge explores ways that interiors both constitute and upset our edges, whether physical, conceptual or psychological, imagined, implied, necessary or discriminatory. The essays in this volume explore these questions in history, theory, and praxis through a focus on different periods, cultures, and places. Interior Design on Edge showcases new scholarship that expands and contests traditional relationships between architecture, interiors, and the people that use and design them, provoking readers to consider the interior differently, moving beyond its traditional, architectural definition. Focusing on the concept of interiority considered in a wider sense, it draws on interdisciplinary modes of investigation and analysis and reflects the latest theoretical developments in the fields of interior design history and practice. With new research from both established and emerging authors, this volume will make a valuable contribution to the fields of Interior Design, Architecture, Art and Design History, Cultural History, Visual Culture Studies, and Urban Studies.
Keywords: ARCHITECTURE / Interior Design / General; Interior architecture -- Psychological aspects